Desenvolvimento de formulações de polímeros biodegráveis a partir da modificação de derivados do milho via extrusão reativa. - Santiago, Paula Dias Lopes (Universidade Federal de São Carlos, 2023)
The human consumption of plastic and the consequent generation of waste has been growing exponentially in the last century, causing several environmental impacts. One of the alternatives to mitigate this effect is the use of biodegradable polymers to replace the commonly used synthetic polymers. Starch is one of the most promising materials for this purpose, considering its low cost, easy obtainment in nature and ability to be chemically, biologically and physically modified. One of the sources of starch is corn and in Brazil its use is extremely attractive due to the high production of this food. However, starch has limited properties in terms of mechanical strength and hydrophilicity. Thus, studies have been carried out to improve the properties of this material, making its processing and application more satisfactory. The inclusion of glycerol, waste from the biodiesel industry, as a plasticizing agent, and coconut oil to increase mechanical strength and resistance to water absorption are noteworthy. Thus, this work investigated the effects of modifying the product derived from corn, pre-gelatinized starch, for the processing of polymers using different concentrations of glycerol and coconut oil through the reactive extrusion process in order to obtain new formulations of biodegradable and renewable source products. Thermal, chemical and mechanical analyzes were carried out, which demonstrated an improvement in the mechanical properties in relation to thermoplastic starch (TPS), with an increase of up to 37.5% in the tensile strength limit and 32.1% in elongation at break, for the concentration of 20.0% coconut oil. Water absorption tests showed that the modified materials showed greater resistance to water absorption due to the incorporation of coconut oil. Total biodegradation in simulated soil was up to 37 days, which is an attractive result as it generates less environmental impact, considering that synthetic polymers take hundreds of years to degrade in the environment.
Development of biodegradable polymer formulations from the modification of corn derivatives via reactive extrusion.
Keywords: Polímeros biodegradáveis; Amido de milho; Glicerol; Biodegradable polymer; Óleo de coco; Starch corn; Glycerol; Coconut oil; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS